WORK STRESS, BURNOUT, AND MENTAL HEALTH: HR STRATEGIES FOR ENHANCING EMPLOYEE WELLBEING - Zikri Helmi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
The contemporary workplace faces a mental health crisis, with rising burnout and stress driven by systemic organizational stressors. This research investigates the role of HR in enhancing employee wellbeing, moving beyond traditional reactive approaches. Using a mixed-methods analysis, we identified unsustainable workloads, role ambiguity, and toxic leadership as primary drivers of psychological distress. While existing interventions like EAPs provide necessary support, they remain limited by low utilization and a failure to address root causes. The study concludes that effective mental health management requires an integrated, proactive HR framework focused on primary prevention through job redesign, leadership development, and cultural change. This strategic shift from treating individuals to building resilient work systems is essential for creating sustainable, high-performing organizations where employee wellbeing is a core strategic asset.